Recombinant protein expression by targeting pre-selected chromosomal loci - Nehlsen, Kristina (BioMed Central, 2009)
BACKGROUND: Recombinant protein expression in mammalian cells is mostly achieved by stable integration of transgenes into the chromosomal DNA of established cell lines. The chromosomal surroundings have strong influences on the expression of transgenes. The exploitation of defined loci by targeting expression constructs with different regulatory elements is an approach to design high level expression systems. Further, this allows to evaluate the impact of chromosomal surroundings on distinct vector constructs. RESULTS: We explored antibody expression upon targeting diverse expression constructs into previously tagged loci in CHO-K1 and HEK293 cells that exhibit high reporter gene expression. These loci were selected by random transfer of reporter cassettes and subsequent screening. Both, retroviral infection and plasmid transfection with eGFP or antibody expression cassettes were employed for tagging. The tagged cell clones were screened for expression and single copy integration. Cell clones producing > 20 pg/cell in 24 hours could be identified. Selected integration sites that had been flanked with heterologous recombinase target sites (FRTs) were targeted by Flp recombinase mediated cassette exchange (RMCE). The results give proof of principle for consistent protein expression upon RMCE. Upon targeting antibody expression cassettes 90-100% of all resulting cell clones showed correct integration. Antibody production was found to be highly consistent within the individual cell clones as expected from their isogenic nature. However, the nature and orientation of expression control elements revealed to be critical. The impact of different promoters was examined with the tag-and-targeting approach. For each of the chosen promoters high expression sites were identified. However, each site supported the chosen promoters to a different extent, indicating that the strength of a particular promoter is dominantly defined by its chromosomal context. CONCLUSION: RMCE provides a powerful method to specifically design vectors for optimized gene expression with high accuracy. Upon considering the specific requirements of chromosomal sites this method provides a unique tool to exploit such sites for predictable expression of biotechnologically relevant proteins such as antibodies.